Der frühe Sprachunterricht muss umkehren – ein Plädoyer für eine „neue” Didaktik. Early language teaching has to change – arguments for introducing “new” didactics. - Olpińska-Szkiełko, Magdalena (Glottodidactica, 2016)
The objective of the article is to present some valid arguments for a “new” didactics of early foreign language teaching. The foreign language teaching in Poland has become an obligatory part of the curriculum in kindergartens and pre-schools (for 5 years-olds), and from the beginning of Sept. 2017 it will also concern all 3 and 4 years old children in pre-school education. Didactic principles and materials for teaching foreign languages that are applied in kindergartens are designed mainly for grade 1-3 of the primary school and cannot be automatically adopted for the earlier educational stages. The didactic process must be founded on linguistic and glottodidactic study of natural language acquisition, bilingualism and bilingual education. In the article some most important differences between the language learning process in the primary school and kindergarten are discussed and conclusions for the shaping of the language teaching and learning situation in pre-schools are drawn. In the last part some selected examples of the “new” teaching forms and activities will be presented.